PENGARUH EFIKASI DIRI, KEPUASAN KERJA, PENGEMBANGAN KARIR TERHADAP PERILAKU KEWARGAAN ORGANISASIONAL PADA GURU SMK/SMA DI KOTA DEPOK - Dwi Wiryanti (2021)
Organizational citizenship behavior is an extra role behavior of organizational members which is carried out on their own accord without expecting a reward to achieve organizational goals for that it is necessary to motivate each individual One of the individuals who support organizational quality in education is a teacher. Teachers are one of the human resources that support the quality of education. This study aims to test, prove and analyze organizational citizenship behavior which is influenced by self-efficacy, job satisfaction and career development for SMK / SMA teachers in Depok City. The sample of this research is 95 SMK / SMA teachers in Depok City as respondents which include teaching staff, education personnel, contract teachers, permanent teachers and civil servant teachers (PNS). The data in this study were obtained through observation and distributing questionnaires via google form. The data analysis technique used in this study was Partial Least Square (PLS). The results of this study indicate that self-efficacy has no effect on organizational citizenship behavior of SMK / SMA teachers in Depok City, job satisfaction affects organizational citizenship behavior of SMK / SMA teachers in Depok City, career development affects organizational citizenship behavior of SMK/SMA teachers in Depok City. . This research has the implication that job satisfaction and career development are important elements to pay attention to in an effort to improve the organizational citizenship behavior of SMK / SMA teachers in Depok City so that it can be used as an example for organizations, schools or other agencies.